Prevalence and biofilm-formation ability of Staphylococcus aureus isolated from livestock, carcasses, the environment, and workers of three abattoirs in Greece - Komodromos, Dimitrios; Kotzamanidis, Charalambos; Giantzi, Virginia; Angelidis, Apostolos S.; Zdragas, Antonios; Sergelidis, Daniel (Journal of the Hellenic Veterinary Medical Society, 2022)
Staphylococcus aureus is one of the leading causes of foodborne intoxications. The pathogen’s biofilm-formation ability facilitates its spread and enhances its tolerance against hostile environments. The objectives of this cross-sectional study were to investigate the prevalence of S. aureus in the received livestock, the corresponding carcasses, the employees and the surfaces of infrastructures and tools in three abattoirs of Northern Greece and to determine the biofilm-forming potential of the recovered isolates. The isolation of presumptive S. aureus isolates from different types of samples was performed using classic microbiological methods and molecular identification to the species level was done via detection of the coa and nuc genes. Biofilm-formation ability was assessed using a semi-quantitative, microtiter plate method. Fifty-five out of 547 samples examined tested positive for the presence of S. aureus. The highest S. aureus isolation frequency was observed from human nasal cavities (17.2%) and tool surfaces (16.1%) followed by pig carcasses (15.5%), small ruminant nasal cavities (15.0%), cattle nasal cavities (7.5%), pig nasal cavities (6.9%), infrastructure surfaces (6.8%), cattle carcasses (5.7%) and small ruminant carcasses (5.0%). The isolation frequency of S. aureus varied considerably (p < 0.05) among the sampled establishments, ranging from 4.2% to 31.7%. All S. aureus isolates were found capable of producing biofilms: 43.6% possessed strong biofilm-formation ability, 54.5% moderate and only one isolate (1.8%) showed weak biofilm-formation ability. The contamination of equipment and tools by biofilm-producing S. aureus emphasizes the need for the application of strict hygiene practices during meat-processing. In addition, the application of an effective and regularly verified sanitation program is necessary to prevent biofilm formation and minimize the risk of carcass contamination.